2019
DOI: 10.1097/md.0000000000016867
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk stratification-based model for prediction of acute kidney injury in critically ill patients

Abstract: Acute kidney injury (AKI) is a complex syndrome with a variety of possible etiologies and symptoms. It is characterized by high mortality and poor recovery of renal function. The incidence and mortality rates of patients with AKI in intensive care units are extremely high. It is generally accepted that early identification and prompt treatment of AKI are essential to improve outcomes. This study aimed to develop a model based on risk stratification to identify and diagnose early stage AKI for improved prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…If the cut-off value of Nomogram score was 119.22, the AUC of this model was 0.9409 with the sensitivity of 85.71%, the specificity of 89.66%, the positive predictive value of 89.29%, and the negative predictive value of 87.10% in the diagnosis of AKI (Figure 3). Its AUC was higher than that reported in previous studies [13][14][15][16][17][20][21][22][23][24][25]. Thus, our model is promising to be used as a tool to identify high-risk patients clinically.…”
Section: Discussionmentioning
confidence: 51%
“…If the cut-off value of Nomogram score was 119.22, the AUC of this model was 0.9409 with the sensitivity of 85.71%, the specificity of 89.66%, the positive predictive value of 89.29%, and the negative predictive value of 87.10% in the diagnosis of AKI (Figure 3). Its AUC was higher than that reported in previous studies [13][14][15][16][17][20][21][22][23][24][25]. Thus, our model is promising to be used as a tool to identify high-risk patients clinically.…”
Section: Discussionmentioning
confidence: 51%
“… 27 28 Another study found that advanced age was an independent risk factor for AKI in hospitalised patients without COVID-19. 29 The viral clearance ability of male patients with SARS-CoV-2 infection is significantly lower than that of female patients with SARS-CoV-2 infection, which may represent one potential reason for the increased severity of symptoms and incidence of complications observed in male patients with SARS-CoV-2 infection. 30 Higher rates of smoking and alcohol consumption, as well as biological differences in the immune system between the sexes, could make men more vulnerable to AKI during SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 97%
“…27 28 Another study found that advanced age was an independent risk factor for AKI in hospitalised patients without COVID-19. 29 The viral clearance ability of male patients with SARS-CoV-2 Figure 4 Forest plot showing the subgroup analysis of risk of death. The Q test showed p>0.1, indicating no heterogeneity existed between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that have included biomarkers do not report a discriminatory capacity for the prediction of kidney injury outcomes. Recently, Chen et al [ 33 ] and Malhotra et al [ 34 ] developed predictive models based mainly on clinical characteristics such as sex, age, hypertension, diabetes, coronary heart disease, heart failure, sepsis, mechanical ventilation, total bilirubin, hypoalbuminemia, emergency surgery, cancer, chronic kidney disease, and exposure to nephrotoxic agents, finding an adequate discriminatory capacity (area under the curve of 0.81). In our study, in addition to the comorbidities included in the Charlson index, variables such as diagnosis of sepsis, heart failure or trauma at admission to the ICU, and the use of contrast media during ICU stay were considered.…”
Section: Discussionmentioning
confidence: 99%